Big Ears Listening for Gender in Jazz Studies - Christina, Baade; Eric, Porter; Farah Jasmine, Griffin; Ingrid, Monson; Jayna, Brown; Jeffrey, Taylor; João H., Costa Vargas; Julie, Dawn Smith; Kristin, McGee; Kun, Josh; Lara, Pellegrinelli; Monica, Hairston; et al. (Refiguring American Music, 2008)
In jazz circles, players and listeners with "big ears" hear and engage complexity in the moment, as it unfolds. Taking gender as part of the intricate, unpredictable action in jazz culture, this interdisciplinary collection explores the terrain opened up by listening, with big ears, for gender in jazz. Essays range from a reflection on the female boogie-woogie pianists who played at Café Society in New York during the 1930s and 1940s to interpretations of how the jazzman is represented in Dorothy Baker's novel Young Man with a Horn (1938) and Michael Curtiz's film adaptation (1950). Taken together, the essays enrich the field of jazz studies by showing how gender dynamics have shaped the production, reception, and criticism of jazz culture.Scholars of music, ethnomusicology, American studies, literature, anthropology, and cultural studies approach the question of gender in jazz from multiple perspectives. One contributor scrutinizes the tendency of jazz historiography to treat singing as subordinate to the predominantly male domain of instrumental music, while another reflects on her doubly inappropriate position as a female trumpet player and a white jazz musician and scholar. Other essays explore the composer George Russell's Lydian Chromatic Concept as a critique of mid-twentieth-century discourses of embodiment, madness, and black masculinity; performances of "female hysteria" by Les Diaboliques, a feminist improvising trio; and the BBC radio broadcasts of Ivy Benson and Her Ladies' Dance Orchestra during the Second World War. By incorporating gender analysis into jazz studies, Big Ears transforms ideas of who counts as a subject of study and even of what counts as jazz.Contributors: Christina Baade, Jayna Brown, Farah Jasmine Griffin, Monica Hairston, Kristin McGee, Tracy McMullen, Ingrid Monson, Lara Pellegrinelli, Eric Porter, Nichole T. Rustin, Ursel Schlicht, Julie Dawn Smith, Jeffrey Taylor, Sherrie Tucker, João H. Costa Vargas